A Little Trouble in Dublin - MacAndrew, Richard (United Kingdom Cambridge University Press, 2009)
Twins, Andy and Mary, are in Dublin on a school trip. When Mary discovers that she has been given a forged €20 note, she thinks she knows the identity of the forger. The twins start to investigate, but it soon becomes clear that the forgers know who Andy and Mary are too.
Cambridge Experience Readers, previously known as Cambridge Discovery Readers, is an exciting series of original fiction, adapted fiction and factbooks, specifically written for pre-teen and teenage learners of English.
Contents
Keywords: Adventure; Language Learning; Reading books; Beginner/Elementary level